Block chain based data security enhanced IoT server platform - Jeon, Jin Hyeong; Kim, Ki Hyung; Kim, Jai Hoon (International Conference on Information Networking, 2018)
In this paper, we propose a new IoT server platform by introducing a block chain and store sensor data in a block chain. Mobius selected IoT server platform, Mobius authenticates IoT devices conforming to oneM2M standard, receives real-time sensor data, stores information and data in Mysql server and manages it. However, Mysql's Mobius configuration has many vulnerabilities and threats to security, and many of them have not been addressed yet. This paper propose a data storage method by constructing a block chain as a database instead of a general / conventional server construction method such as Mysql server in the server configuration method by introducing such a block chain.
Keywords: Construction method; Data storage; Iot devices; Onem2m standards; Real time sensors; Security; Sensor data; Server platform; Block Chain; Database; IoT; Security